Electric field enhances mixing in micro circular pipes - Ding, Zijing (2018)
Mixing of two miscible flows with a radial conductivity stratification in a micro-pipe can be enhanced by an axial electric field. The mechanism is interpreted by a linear stability analysis. The effect of ionic diffusion on rapid mixing between the two liquids is discussed. A case study shows that, when the conductivity in the inner layer is larger, the growth rate becomes smaller as the electrical Schmidt number increases; when the conductivity in the outer layer is larger, the growth rate either decreases or increases as the electrical Schmidt number increases.